2015
DOI: 10.4187/respcare.03837
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Flow Nasal Cannula for Acute Dyspnea and Hypoxemia in the Emergency Department

Abstract: BACKGROUND: Acute dyspnea and hypoxemia are 2 of the most common problems in the emergency room. Oxygen therapy is an essential supportive treatment to correct these issues. In this study, we investigated the physiologic effects of high-flow nasal oxygen cannula (HFNC) compared with conventional oxygen therapy (COT) in subjects with acute dyspnea and hypoxemia in the emergency room. METHODS: A prospective randomized comparative study was conducted in the emergency department of a university hospital. Forty sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 34 publications
(36 reference statements)
8
115
1
1
Order By: Relevance
“…40 HFNC has also been applied to patients with mild to moderate hypoxemic respiratory failure in a cardiothoracic ICU 12 and emergency room. 69,82,83 HFNC can be regarded as a first-line treatment for patients with mild to moderate hypoxemic ARF.…”
Section: Hypoxemic Respiratory Failurementioning
confidence: 99%
“…40 HFNC has also been applied to patients with mild to moderate hypoxemic respiratory failure in a cardiothoracic ICU 12 and emergency room. 69,82,83 HFNC can be regarded as a first-line treatment for patients with mild to moderate hypoxemic ARF.…”
Section: Hypoxemic Respiratory Failurementioning
confidence: 99%
“…The latter may be due to a lack of predefined discontinuation criteria, distraction and/or missed cues, inexperience with the device and its use, or a desire to avoid escalation due to patient or provider bias. The current studies by Nagata et al, 7 Gaunt et al, 8 Rittayamai et al, 9 and Vargas et al 10 failed to define such abandonment criteria, and in particular, Rittayamai et al 9 acknowledge several such limitations of their study. First, a median 1.5 h elapsed between recognition and implementation of HFNC or conventional oxygen therapy.…”
Section: Cautions and Limitations In The Use Of Hfncmentioning
confidence: 55%
“…HFNC addresses these shortcomings through delivery of high flow (30 -60 L/min) heated and humidified gas at a constant F IO 2 via a wide-bore nasal interface. 3 Its comfort has been wellestablished, including in the current study of emergency department subjects by Rittayamai et al, 9 and correlates with patient compliance.…”
Section: In Support Of Hfnc For Acute Respiratory Failurementioning
confidence: 99%
See 1 more Smart Citation
“…HFNC was also usually better tolerated than NIV, although NIV obtained greater improvements in oxygenation [13,14]. In addition, HFNC has been used in small cohorts of patients with acute respiratory failure in the emergency department [15,16] and even in 150 children less than 2 years old during interhospital transport [17]. The effects on oxygenation and rates of intubation reported in all these studies are similar to those found when HFNC has been used in patients with acute respiratory failure admitted to critical care areas, suggesting that, with adequate monitoring, HFNC can be safely used outside the critical care setting.…”
Section: Clinical Datamentioning
confidence: 99%